Can Spectral Power Be Used as a Candidate Seizure Marker of the Periodic Discharges Pattern? - Chen, Jianhua; Zhou, Xiangqin; Jin, Liri; Lu, Qiang; Sun, Heyang; Liu, Qing; Huang, Yan (Frontiers in Neurology, 2021)
Introduction: It remains controversial whether the periodic discharges (PDs) pattern is an ictal or interictal phenomenon. The aims of the study are to apply time-frequency and power spectrum analysis to study the PDs pattern and prediction of seizures. Methods: We retrospectively searched continuous electroencephalography (cEEG) recordings to identify patients exhibiting the PDs pattern. Artifact-free cEEG segments demonstrating the PDs pattern with stable baselines were chosen for time-frequency and power spectrum analysis. Results: In total, 72 patients (1.3%) exhibited the PDs pattern, with a mean age 36.0 ± 20.7 years (range, 8–76 years). The median spectral power of PDs with a length of 60s was 70.94 μV2 and that of PDs with a length of 20s was 195.80 μV2. During follow-up, patients with spectral power of PDs of length 60s and 20s lower than 28.65 μV2 and 36.09 μV2, respectively, exhibited no seizure. For predicting seizures, when the spectral power for PDs of 60 s or 20 s was greater than 17.26 μV2 or 21.40 μV2, the diagnostic sensitivity was 100%, and specificity was 86%. The locations of maximal spectral power of PDs, seizure onset zone (SOZ) judged from scalp EEG, and the most prominent regions of hyper- or hypo-metabolism on FDG-PET were congruent. Conclusions: Spectral power might be a candidate seizure marker of the PDs pattern. High spectral power indicated a high risk of seizures, and low spectral power was associated with a low risk of seizures.